Marketing Analysis Identify Internal and External Factors of Coffee Products (Mountain Karamat Village, Sukabumi District) - Agung Zulfikri; Yusuf Iskandar; Kurniawan Kurniawan (West Science Business and Management, 2023)
Gunung Karamat Village is a border village between West Java Province and Banten Province, with a distance of 30 km to the center of the Sukabumi Regency government, which is located at Pelabuhan Ratu, with an area of 14.80 km2. Besides that. Gunung Karamat village has a coffee plantation whose quality is very promising. This is the result of a joint struggle between the community and the village government in managing agricultural land. Gunung Karamat village has superior products, namely robusta and arabica coffee. This has opened the eyes of the Sukabumi Mandiri Regional Public Company (Perumda ASM). The data collection method is the observation method, which is one method of collecting data by making direct observations, explaining and describing internal and external conditions (SWOT). The interview method was carried out with coffee managers such as BUMDES Gunung Karamat by asking questions that had been prepared previously. Data analysis was carried out with qualitative methods. The factors of excellence in this Gunung Keramat village coffee product are the availability of a very large area, the brand of Gunung Keramat coffee is well known, and the location of the coffee planter is very suitable. of the deficiency factors, namely, inadequate road access, incompetent experience of coffee farmers and limited capital are factors for slow Mount Karamat coffee.